2019
DOI: 10.7717/peerj.6537
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of metal and antibiotic resistant traits in novel β-ProteobacteriumAchromobacter xylosoxidansBHW-15

Abstract: Chromosomal co-existence of metal and antibiotic resistance genes in bacteria offers a new perspective to the bacterial resistance proliferation in contaminated environment. In this study, an arsenotrophic bacteriumAchromobacter xylosoxidansBHW-15, isolated from Arsenic (As) contaminated tubewell water in the Bogra district of Bangladesh, was analyzed using high throughput Ion Torrent Personal Genome Machine (PGM) complete genome sequencing scheme to reveal its adaptive potentiality. The assembled draft genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…The electrochemical detection process of As (III) transformation is shown in Fig. 7 a and a model representing the molecular interaction of A. xylosoxidans BHW-15 with the arsenic species is proposed based on both the experimental findings of this study and the genome sequence of A. xylosoxidans BHW-15 26 (Fig. 7 b).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The electrochemical detection process of As (III) transformation is shown in Fig. 7 a and a model representing the molecular interaction of A. xylosoxidans BHW-15 with the arsenic species is proposed based on both the experimental findings of this study and the genome sequence of A. xylosoxidans BHW-15 26 (Fig. 7 b).…”
Section: Resultsmentioning
confidence: 98%
“…The genome of BHW-15 carried two operons—aioSXBA (oxidation) and arsRCAD (reduction). Cytoplasmic reduction of As (V) to As (III) is occurred by the ArsC protein leading to subsequent extrusion via ArsB or ArsAB pump is pumped out from the cell by efflux pump specific ArsB transporter while, aio operon regulates the oxidation of the arsenite to arsenate inside the cell in presence of periplasmic arsenite oxidase (aioBA) enzyme and pumps it out form the cell using unknown efflux pump (Istiaq et al 26 ). We found the oxidation process of As (III) to As (V) by A. xylosoxidans BHW-15 was predominant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Resende et al [ 86 ] demonstrated that clinical isolates of C. davisae exhibiting tolerance towards Ni, Zn, Cr, Cu, Cd and Hg, acquires a selection pressure towards a group of antibiotics. In another study, Istiaq et al [ 87 ] reported that strains of A. xylosoxidans possess genes for Arsenic (As), Cu, Zn, and Cd resistance, which also display a broad range of resistance against antibiotics belonging to β-lactams, aminoglycosides, cephalosporins, monobactams and even macrolides. Genomic investigation of S. maltophilia SJTH1 isolated from the hospitalized patient of PGIMER, Chandigarh, India revealed diverse antibiotic resistance genes, efflux pumps, heavy metal resistance, various transcriptional regulators etc.…”
Section: Discussionmentioning
confidence: 99%